Pengaruh Person Organization Fit terhadap Komitmen Organisasi - Hardani Dwi Jayanti (Institut Agama Islam Neegri Madura, 2022)
Organizational commitment is defined as the degree to which employees have confidence in and accept organizational goals or organizational regulations, and are willing to stay with the company or leave the company. The cause of the commitment that is not owned by this individual will lead to the problem of leaving employees and the side of social organization that provides discomfort. The impact of this commitment and suitable person organization provides a positive side for the company in terms of organizational culture. The purpose of this organizational commitment is to find out the factors that influence the organization according to employees in terms of the employee's organizational culture with the company. So that it will reduce the problems that exist in the company because of individual incompatibility with the company. The benefits of research on a more comprehensive study of organizational commitment and people are expected to provide more comprehensive knowledge for science.